Pengembangan Pangan Tradisional Berbasis Jagung Mendukung Diversifikasi Pangan - Suarni Suarni (Puslitbang Tanaman Pangan, 2013)
Various corn-based traditional food in Indonesia representing a wealth ethnic food in every regions that needs to be preserved. In every region there is a specific corn based food, differ in processing methods. This paper discusses various traditional food products based on fresh corn and dried grain. Nutritional components of local corn variety were also reviewed. To improve the image of traditional corn based food an intensive promotion of the functional food contained in the simple corn food preparation is suggested. It requires that corn food be sold in food stalls and restaurants. Corn based food is considered healthier, low in cholesterol and suitable for the old people diet. Traditional food preparation based on corn could be modified using the international recipes, so that it could enter the home industries. Corn variety suitable for food industries is needed, especially those with good eating quality, high productivity and contain high nutritions. Corn based food should be promoted to broaden the food diversification program.